Implementation of Cyber Counseling for Increase Accessibility of Service Counseling - Siti Juariah; Muhammad Cholid Abdurrohman (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
In the digital era, the need for easily accessible counseling services is increasing, especially for individuals facing geographic and mobility limitations. This study aims to explore the implementation of cyber counseling as an alternative to increase the accessibility of counseling services. The method used is a literature study by analyzing relevant scientific articles, reports, and academic sources related to cyber counseling and access to mental health services. Data sources were obtained from the Google Scholar database with a publication range of 1988–2024, using the keywords "cyber counseling services", "global cyber counseling era", and "cyber counseling in schools". Data analysis was conducted qualitatively through the stages of data reduction, data presentation, and drawing conclusions. The results of the analysis indicate that cyber counseling has great potential in expanding access to counseling services, especially for groups who have difficulty accessing face-to-face services. However, its implementation still faces challenges, particularly related to data privacy and security, as well as counselor readiness and competence in utilizing technology effectively. These findings emphasize the need for more serious attention to technical and ethical aspects so that cyber counseling can be implemented optimally and sustainably.